Perception of Academic Writing in University Students - Barreda-Parra, Aymé; Núñez-Pacheco, Rosa; Turpo-Gebera, Osbaldo; Diaz-Zavala, Rocío; Esquivel-Las Heras, Janeth (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Academic writing is crucial in university education, yet it also presents a challenge, as writing skills are not always optimal. This study describes students' perceptions of academic writing. A non-experimental descriptive approach was employed, using the Academic Literacy Perception Questionnaire with 295 students in three university programs: Education, Literature and Linguistics, and Psychology. The findings reflect a positive assessment of their communicative competence, indicating that the acquired knowledge has enhanced their writing process and identification of various genres. Simultaneously, students recognize the need to delve deeper into writing strategies.